A comparative study of parallel and distributed Java projects for heterogeneous systems - Al-Jaroodi, J.; Mohamed, N.; Hong Jiang; Swanson, D. (Proceedings: International Parallel and Distributed Processing Symposium: April 15-19, 2002, Ft. Lauderdale, Florida, USA, 2002)
During the last few years, the concepts of cluster computing and heterogeneous networked systems have received increasing interest. The popularity of using Java for developing parallel and distributed applications that run on heterogeneous distributed systems has also grown rapidly. This paper is a survey of the current projects in parallel and distributed Java. These projects’ main common objective is to utilize the available heterogeneous systems to provide high performance computing using Java. These projects were studied, compared and classified based on the approaches used. The study shows three major approaches. One is to develop a system that replaces the Java virtual machine (JVM) or utilizes the available parallel infrastructure such as MPI or PVM. Another is to provide seamless parallelization of multi-threaded applications. The third is to provide a pure Java implementation by adding classes and features that support parallel Java programming. In addition, a number of open issues are identified and discussed in this paper.